2011
DOI: 10.1007/s10404-011-0876-4
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of an optically driven pH gradient generator based on self-assembled proton pumps

Abstract: Optically manipulating the local pH of a target solution in a microchannel, or reservoir, provides a mechanism for activating and controlling a variety of biological and chemical processes on Lab-on-a-Chip (LOC) devices and micro-total analysis systems (l-TAS). A microscale pH gradient generator that exploits the lightactivated molecular proton pumps found in the purple membranes (PM) of bacteriorhodopsin is described in this paper. The photo-electro-chemical transducer is an ultrathin layer (*13 nm) of orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Prior studies have shown that biotin labeling is highly effective and can produce a very thin bR PM layer that is <13 nm [16,22]. Figure 3 shows SEM photographs of the self-assembled ultra-thin bR films on the biofunctionalized PAA substrate at different magnifications.…”
Section: Light Driven Br-paa Transducermentioning
confidence: 99%
“…Prior studies have shown that biotin labeling is highly effective and can produce a very thin bR PM layer that is <13 nm [16,22]. Figure 3 shows SEM photographs of the self-assembled ultra-thin bR films on the biofunctionalized PAA substrate at different magnifications.…”
Section: Light Driven Br-paa Transducermentioning
confidence: 99%
“…There are examples of the successful application of microbial rhodopsin proton pumps such as BR and proteorhodopsin for the light‐driven control of pH in aqueous solutions using pro‐ and eukaryotic cells, [ 8 ] proteoliposomes, [ 9 ] polymerosomes, [ 10 ] and functionalized surfaces. [ 11 ] From a bioenergetical and engineering point of view the combination of light‐driven proton pumps with ATP synthesis utilizing an established proton gradient across a membrane as a power source is an important achievement. [ 12 ] To the best of our knowledge, the utilization of two proton pumps positioned in opposite orientations within the membrane for controlling proton gradients in synthetic systems has not been reported.…”
Section: Introductionmentioning
confidence: 99%